How important are labor market institutions for labor market performance in transition countries? - Hartmut Lehmann; Alexander Muravyev (Institute for the Study of Labor (IZA), 2009)
This paper offers a first comprehensive study of the relationship between labor market institutions and policies and labor market performance in the countries of Eastern Europe and Central Asia, which in the last two decades experienced radical economic and institutional transformations. Based on a new and unique hand-collected dataset, the paper first documents the evolution of labor market institutions and policies in the transition region. The data show a clear trend towards liberalization of labor markets, especially in the countries of the former Soviet Union, but also substantial differences across the countries studied. Second, the paper takes advantage of the large variation in the key economic and institutional variables to test several predictions concerning the role of institutions and polices in explaining labor market outcomes. The results of our econometric analysis are generally consistent with the view that institutions matter for labor market outcomes, and that deregulation of the labor markets improves their performance. The analysis also suggests several significant interactions between different institutions, which are in line with the idea of reform complementarity and broad reform packages. We also show that there are important advantages of focusing on a broader set of labor market outcomes, and not only on the unemployment rate, which until now has been the main approach in the empirical literature.
Keywords: E24; J21; P20; 330; Labor market institutions; unemployment; transition economies; Arbeitsmarktflexibilisierung; Übergangswirtschaft; Arbeitsmarkt; Institutioneller Wandel; Arbeitslosigkeit; Transformationsstaaten; Osteuropa; Zentralasien